A review of the subspecies of the Leach petrel, Oceanodroma leucorhoa (Vieillot) - Oberholser, Harry C. (Harry Church) (Smithsonian Institution Press, [etc.], 1917)
(Uploaded by Plazi from the Biodiversity Heritage Library) No abstract provided.